2015
DOI: 10.1309/ajcp1na3ychcdeig
|View full text |Cite
|
Sign up to set email alerts
|

Blood Flow Cytometry in Sézary Syndrome

Abstract: We confirm the relevance of CD26 negativity in SS diagnosis and monitoring. Nevertheless, the presence of rare CD26+ cases suggests that a multiparameter flow cytometry approach should be used. Changes in methylation profile could account for phenotypical heterogeneity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 44 publications
4
17
0
Order By: Relevance
“…The prognostic value of a cell surface marker may vary with treatment. Novelli et al., found SzS patients who had a presence of a variable proportion of CD26+ atypical cells at diagnosis showed a statistically significant higher overall survival. However, in their retrospective cohort study of eleven MF/SzS patients who had undergone treatment, Vandersee et al .…”
Section: Cell Surface Markersmentioning
confidence: 98%
See 1 more Smart Citation
“…The prognostic value of a cell surface marker may vary with treatment. Novelli et al., found SzS patients who had a presence of a variable proportion of CD26+ atypical cells at diagnosis showed a statistically significant higher overall survival. However, in their retrospective cohort study of eleven MF/SzS patients who had undergone treatment, Vandersee et al .…”
Section: Cell Surface Markersmentioning
confidence: 98%
“…Novelli et al, [50] found SzS patients who had a presence of a variable proportion of CD26+ atypical cells at diagnosis showed a statistically significant higher overall survival. However, in their retrospective cohort study of eleven MF/SzS patients who had undergone treatment, Vandersee et al [51] calculated a low positive predictive value for changes in CD26 expression and clinically meaningful events.…”
Section: Cell Surface Markersmentioning
confidence: 99%
“…With the recognition that neoplastic T cells have diminished expression of CD26 in about 90% of Sézary patients, the percentage and absolute numbers of CD4 + CD26lymphocytes have recently been proposed to define B ratings [18,21]. However, because CD26 may be variably expressed (some neoplastic cells positive, some negative), it is useful to also measure CD4 + CD7cells and to use this value if it exceeds the percentage of CD4 + CD26cells [27].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to demonstrating clonally related neoplastic T cells in the skin and PB, one or more of the following criteria are required to diagnose SS: an absolute Sézary cell count ≥1,000/µL; an expanded CD4 + T-cell population resulting in a CD4 : CD8 ratio of ≥10; or the loss of one or more T-cell antigens. Because of the morphologic heterogeneity of Sézary cells, flow cytometric analysis of PB is essential for diagnostic purposes and tumor burden monitoring during follow-up [2,3]. Typical Sézary cells have a CD3 + CD4 + CD8phenotype and characteristically lack CD7 and CD26 [4].…”
Section: Introductionmentioning
confidence: 99%